Pengaruh Perbedaan Jenis Pelarut Terhadap Kadar Flavonoid Total Ekstrak Daun Sirsak (Annona muricata L.): The Effect of Different Types of Solvents on Total Levels of Flavonoid Extract (Annona muricata L.) - Ni Ketut Linda Puspa Yani; Kunti Nastiti; Noval Noval (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
One of the plants that is efficacious to prevent a disease is the leaf Annona muricata L. This plant contains contains saponins, terpenoids, steroids, flavonoids, tannins and alkaloids. Compounds that have the most role in causing pharmacological effects are flavonoid compounds as a source of antioxidants. The level of polarity of the solvent in the study will affect the content of the compound extracted based on the principle of like dissolves like. This study was conducted to determine the total flavonoid content at different levels of solvent types and the effect of different solvents of 96% ethanol, ethyl acetate and n-hexane on total flavonoid content. In addition, qualitative tests were carried out to determine the flavonoid compounds. The type of research used is pre-experimental, extraction with controlled maceration method of temperature, light, length of time and stirring. Qualitative analysis with color correction test and Thin Layer Chromatography. Assay using UV-Vis spectrophotometry. The results of the research on identification by color test and Thin Layer Chromatography on the extract Annona muricata L. using 96% ethanol, ethyl acetate and n-hexane as solvents were positive for flavonoids and the results of the determination of flavonoid levels in each solvent were 68,9048 mgQE/g, 97,2381 mgQE /g and 73,6667 mgQE/g. ANOVA statistical analysis in each group had a significant difference with p= <0.001 (<0.05). Flavonoid compounds are influenced by the level of solvent polarity, there are significant differences between treatment groups with different types of solvents on total flavonoid levels. The highest flavonoid content was found in ethyl acetate followed by n-hexane and 96% ethanol.